Electrochemical Characteristics of Capacitor Systems Formed on Chemically Modified Carbon Base - Ostafiychuk, B.K.; Budzulyak, I.M.; Mandzyuk, V.I.; Lisovskyy, R.P. (Наносистеми, наноматеріали, нанотехнології, 2008)
Influence of chemical modification of the activated carbon (AC) material on its specific capacity is found out with the use of methods of impedance spectroscopy, cyclic voltammetry and chronopotentiometry. As shown, a general capacity is the sum of two components, namely, double electric-layer (DEL) capacity and pseudocapacity, thus the deposit of the last is insignificant (8—14%). The alloying with rare-earth metals and their compounds results in the rise of specific capacity of AC. Probably, the principal reason of such a growth is transformation of valence bond of carbon material due to introduction of the additional electron states from the implanted metals. As a result, the considerably greater amount of ions (especially, positive ones) will take part in DEL forming, and, consequently, will predetermine growth of specific capacity.